ANALISIS KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA SMA KELAS XI PADA MATERI TRIGONOMETRI DI TINJAU DARI SELF CONFIDENCE - Iis Trisnawati; Wulan Pratiwi; Puji Nurfauziah; Rippi Maya (IKIP Siliwangi, 2018)
The purpose of this study is to analyze mathematic creatively thinking and analyze students' difficulties in solving the problem of mathematical creative thinking on Trigonometric material in review of self confidence. The subjects of this study were students of class XI MAN Kota Cimahi that consists of 27 students. The method used in this research is descriptive method with qualitative approach. The stage of this research consists of five stages, including: filling self confidence, tests of mathematical creative thinking ability, interviews, analysze and take a conclusions. The results of the research showed that, when that self confidence affect the improvement of mathematical creative thinking in students. The higher self confidence in the students, the curiosity of students will be encouraged and will increase the ability of creative thinking mathematics. Otherwise, if the self confidence in students is lower, than the student's curiosity is less encouraged and this will have an impact to increase the ability to think creative mathematics.